Synthesis of corrosion inhibitive poly(2,5-dimethylaniline) coatings on low carbon steel - Shinde, V.; Sainkar, S. R.; Gangal, S. A.; Patil, P. P. (Journal of Materials Science, 2006)
An attempt has been made towards the synthesis of strongly adherent poly(2,5-dimethylaniline) coatings on low carbon steel substrates, with an objective of examining the possibility of using this polymer for corrosion protection of steel in chloride environment. In this work, the poly(2,5-dimethylaniline) coatings were synthesized by electrochemical polymerization of 2,5-dimethylaniline using sodium salicylate as a supporting electrolyte. The characterization of these coatings was carried out by cyclic voltammetry, UV-visible absorption spectroscopy, Fourier transform infrared spectroscopy and scanning electron microscopy. The results of these characterizations indicate that the aqueous salicylate solution is a suitable medium for the electrochemical polymerization of 2,5-dimethylaniline to generate strongly adherent and smooth poly(2,5-dimethylaniline) coatings on low carbon steel substrates. The performance of poly(2,5-dimethylaniline) as protective coating against corrosion of low carbon steel in aqueous 3% NaCl was assessed by the open circuit potential and the potentiodynamic polarization measurements. The potentiodynamic polarization measurement reveals that the poly(2,5-dimethylaniline) coating increases the corrosion potential and reduces the corrosion rate of low carbon steel almost by a factor of 50. This study clearly ascertains that the poly(2,5-dimethylaniline) has outstanding capability to protect low carbon steel against corrosion in chloride environment. (c) 2006 Springer Science + Business Media, Inc.